METHOD OF PROJECTS AND FORMATION OF KEY COMPETENCES (Pedagogy of Higher and Secondary Education, 2011)
Method of project is detailed in the aspect of the formation of core competencies.
Keywords: method of project; competentions; innovative approaches; cognitive interests; system of education